Direct Semiconductor Laser Writing of Few‐Layer Graphene Polyhedra Networks for Flexible Solid‐State Supercapacitor. (21st May 2018) - Liu, Chunlin; Liang, Hongwei; Wu, Dun; Lu, Xiangyu; Wang, Qiang
Abstract: Here, a simple one‐step fabrication methodology is presented for continuous heteroatoms‐doped carbon polyhedra networks via direct semiconductor laser writing on polyimide sheets. It is found that these nanosized polyhedra are nonporous solids and comprised of few‐layer graphene. By the adoption of lithium containing polymer gel electrolyte, flexible solid‐state supercapacitors are designed and assembled in planar and interdigitated configuration with the irradiated plastic sheets as electrodes. When compared to their counterparts with the acid gel electrolyte, they exhibit high areal specific capacitance up to 34.7 mF cm −2 (vs ≈8 mF cm −2 ) at the current density of 0.1 mA cm −2 . This substantial enhancement is considered to be due to the combination of Faradaic intercalation and non‐Faradaic absorption of the Li‐ions at the carbon polyhedra membrane electrodes. With the improvement of energy density, the complex of supercapacitor device is capable of lighting the liquid crystal display of a commercial hygrometer for ≈1 min. Abstract : A patterned carbonaceous membrane packed together with nanopolyhedra is fabricated by semiconductor laser writing on polyimide sheets . The flexible solid‐state supercapacitors assembled with Li‐containing gel electrolyte (poly(vinyl alcohol)/LiCl) showcase a higher areal specific capacitance in contrast to their acid gel electrolyte counterparts. This substantial enhancement is considered to be due to the combination of Faradaic intercalation and non‐Faradaic absorption of the Li‐ions.